Effect of wearing an N95 respirator on infrared tympanic membrane temperature measurements - Kim, Jung-Hyun (J Clin Monit Comput, 2014)
To determine the impact of wearing an N95 filtering facepiece respirator (N95 FFR) on tympanic temperature measurements. TMT measurements, with and without wearing an N95 filtering facepiece respirator (N95 FFR) were obtained at the onset and termination of 1 h of treadmill exercise in 21 subjects, and at staggered time intervals (0, 20, 40, 60 min) during combined sedentary activity and exercise of another 46 subjects, to determine any effect on TMT. A total of 877 TMT measurements were obtained that demonstrated a mean TMT increase of 0.05 °C in the first study group (p = 0.04) and a 0.19 °C decrease in the second study group (p < 0.001) with the wearing of an N95 FFR, both of which were lower than controls. Wearing an N95 FFR for 1 h, at different levels of activity, results in significantly lower TMT values than not wearing an N95 FFR, but the magnitude of the changes would likely have minimal clinical significance.